2019
DOI: 10.3390/sym11030340
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Intention of Fintech Services for Bank Users: An Empirical Examination with an Extended Technology Acceptance Model

Abstract: Along with the development of Fintech, many scholars have studied how information technology is applied to financial services with a focus on extended methods for application. Few scholars have studied the influence mechanism behind the adoption of Fintech services. This paper proposes an improved technology acceptance model (TAM) that incorporates user innovativeness, government support, brand image, and perceived risk as determinants of trust to investigate how users adopt Fintech services. We designed a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
353
6
30

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(543 citation statements)
references
References 74 publications
(94 reference statements)
50
353
6
30
Order By: Relevance
“…Usefulness will determine the attitude towards using which will affect the intension to use. The statement is supported by older studies that find that Usefulness have a significant impact towards Attitude towards using [10]…”
Section: Perceived Usefulnessmentioning
confidence: 69%
See 2 more Smart Citations
“…Usefulness will determine the attitude towards using which will affect the intension to use. The statement is supported by older studies that find that Usefulness have a significant impact towards Attitude towards using [10]…”
Section: Perceived Usefulnessmentioning
confidence: 69%
“…They are still worried and doubt the safety of the transaction [6]. Previous researches showed that this variable had significant effect on attitude toward using [10]…”
Section: Brand and Service Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart phone users in India has been ranked 3rd in the world and provides ample opportunities for Fintech companies [11]. Fintech helps not only to consolidate information technology with financial services but also to administer the latest technology in performing traditional financial services [12].…”
Section: Prior Researchmentioning
confidence: 99%
“…Adapun dua variabel tersebut yaitu persepsi kegunaan (perceived usefulness) dan persepsi kemudahan penggunaan (perceived ease of use). Persepsi kegunaan adalah faktor yang banyak digunakan dalam proses adopsi sistem informasi dan didefinisikan sebagai sejauh mana pengguna sistem menggunakan teknologi atau sistem informasi maka akan dapat meningkatkan efisiensi kerja pengguna tersebut (Hu, Ding, Li, Chen, & Yang, 2019). Selanjutnya Doll Et al., (1998) PT.…”
Section: Pendahuluanunclassified